2003
DOI: 10.1034/j.1600-0420.2003.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

A conservative blepharoplasty may be a means of alleviating dry eye symptoms

Abstract: ABSTRACT.Purpose: Patients with dermatochalasis often complain of dry eye symptoms. In a prospective study, the influence of upper eyelid blepharoplasty on dry eye symptoms, tear film parameters and ocular surface morphology was evaluated. Methods: Patients with upper eyelid dermatochalasis were studied before and 3 months after upper eyelid blepharoplasty. Changes in ocular symptoms and physical examinations such as tear film break-up time, Schirmer test without local anaesthesia, impression cytology of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 14 publications
(11 reference statements)
2
28
0
6
Order By: Relevance
“…A literatura é controvérsia com relação à produção da lágrima após a blefaroplastia. Alguns autores (25)(26)(27) observaram diminuição na produção da lágrima e outros (28)(29)(30) , incluindo o presente estudo, observaram um aumento, mostrado pelo resultado no teste de Schirmer no pós-operatório. Ainda que se desconheça tal razão, Kim et al (28) procuram explicar este resultado com a possibilidade de uma reinervação palpebral (supraorbital e supratroclear) pós-operatória que estimularia a divisão oftálmica do V par craniano, afetando desta maneira o nervo lacrimal.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A literatura é controvérsia com relação à produção da lágrima após a blefaroplastia. Alguns autores (25)(26)(27) observaram diminuição na produção da lágrima e outros (28)(29)(30) , incluindo o presente estudo, observaram um aumento, mostrado pelo resultado no teste de Schirmer no pós-operatório. Ainda que se desconheça tal razão, Kim et al (28) procuram explicar este resultado com a possibilidade de uma reinervação palpebral (supraorbital e supratroclear) pós-operatória que estimularia a divisão oftálmica do V par craniano, afetando desta maneira o nervo lacrimal.…”
Section: Discussionunclassified
“…Acreditamos ser devido a uma diminuição da reação inflamatória, uma melhora no campo visual superior e a uma redução do uso dos músculos frontal e levantador da pálpebra. Outra razão pode ser que a diminuição do tônus destes músculos leve a uma melhora na frequência de piscar, o que ajuda na troca do filme lacrimal (29) . No entanto Abell et al (23) não relacionam a blefaroplastia a alterações no mecanismo de piscar.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The frequency of dry eye after blepharoplasty is higher among individuals with preoperative tear insufficiency, but it may also develop due to insufficient postoperative blinks and lagophthalmos. In previous studies, the reported frequency of dry eye following blepharoplasty ranged between 8% and 21% (5,6). Aside from the possible negative cosmetic outcomes, such as eyelid asymmetry, lagophthalmos, or changes in facial expression, complications such as dry eye syndrome and superior limbic keratoconjunctivitis may also emerge after blepharoplasty, and retro-orbital bleeding is a potential complication that may, in rare cases, result in vision loss (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…O filme lacrimal foi classicamente descrito por Wolff, em 1946, como uma estrutura de 7-10µ de espessura, formada por três camadas: lipídica externa (0,1µ), aquosa intermediária (7-10µ) e mucosa interna (0,02-0,05µ). Estudos mais recentes descrevem apenas duas camadas, uma lipídica externa e uma camada gel-aquosa (6) . As funções atribuídas ao filme lacrimal são: prevenção do ressecamento e lubrificação da superfície ocular, atividade antibacteriana, oxigenação e nutrição, formação de superfície óptica refrativa, além de função neutralizadora das substâncias com pH ácido.…”
Section: Resumo Introduçãounclassified